ASEAN Centrality in Asian Regional Architecture - Frassminggi Kamasa (Institute of International Studies, 2014)
This study examines the regional architecture process in Asia. Specifically, I empirically focus on what ASEAN’s role in contemporary Asian regional architecture is and what challenge and opportunities lie ahead. In contrast to other studies, I consider whether the ASEAN as a driving force of the regional architecture in Asia should only be considered in an over-arching macro-analytical sense in order to contain China. Such an approach to the concept may not work in explaining what change in Asia and its relations with the ASEAN centrality. Additionally, I consider why there is a need for regional architecture in Asia. Using a single-case analysis of ASEAN role in regional architecture from 2009-2012, I found evidence of an association between bargaining and mutual satisfaction while embracing different motives and power for doing regional architecture. Moreover, I demonstrate that it makes sense to talk about regional identity whenever ASEAN is struggling to project a common voice.